Systematic Review of the Application of Perinatal Derivatives in Animal Models on Cutaneous Wound Healing - Pichlsberger, Melanie; Jerman, Urška Dragin; Obradović, Hristina; Tratnjek, Larisa; Macedo, Ana Sofia; Mendes, Francisca; Fonte, Pedro; Hoegler, Anja; Sundl, Monika; Fuchs, Julia; Schoeberlein, Andreina; Kreft, Mateja Erdani; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Knowledge of the beneficial effects of perinatal derivatives (PnD) in wound healing goes back to the early 1900s when the human fetal amniotic membrane served as a biological dressing to treat burns and skin ulcerations. Since the twenty-first century, isolated cells from perinatal tissues and their secretomes have gained increasing scientific interest, as they can be obtained non-invasively, have anti-inflammatory, anti-cancer, and anti-fibrotic characteristics, and are immunologically tolerated in vivo. Many studies that apply PnD in pre-clinical cutaneous wound healing models show large variations in the choice of the animal species (e.g. large animals, rodents), the choice of diabetic or non-diabetic animals, the type of injury (full-thickness wounds, burns, radiation-induced wounds, skin flaps), the source and type of PnD (placenta, umbilical cord, fetal membranes, cells, secretomes, tissue extracts), the method of administration (topical application, intradermal/subcutaneous injection, intravenous or intraperitoneal injection, subcutaneous implantation), and the type of delivery systems (e.g. hydrogels, synthetic or natural biomaterials as carriers for transplanted cells, extracts or secretomes). This review provides a comprehensive and integrative overview of the application of PnD in wound healing to assess its efficacy in preclinical animal models. We highlight the advantages and limitations of the most commonly used animal models and evaluate the impact of the type of PnD, the route of administration, and the dose of cells/secretome application in correlation with the wound healing outcome. This review is a collaborative effort from the COST SPRINT Action (CA17116), which broadly aims at approaching consensus for different aspects of PnD research, such as providing inputs for future standards for the preclinical application of PnD in wound healing.